Novel Minimally Invasive Proximal Phalanx Osteotomy for Recurrent Plantar Diabetic Foot Ulcers of Hallux: A Case Series Describing a Novel Technique - TV Raja; Ashwin Annamalai Raja (Journal of Foot and Ankle Surgery (Asia Pacific))
Background: Diabetic foot ulcers (DFUs), especially recurrent plantar ulcers under the hallux, are a major clinical challenge. Minimally invasive techniques, such as proximal phalanx osteotomy, would offer promising outcomes in terms of ulcer healing and reduced recurrence. Objective: To evaluate the efficacy of minimally invasive proximal phalanx osteotomy in diabetic patients with recurrent or nonhealing plantar ulcers under the interphalangeal joint of the hallux. Methods: This retrospective case series included 20 patients with type 2 diabetes who underwent minimally invasive proximal phalanx osteotomy. Patients were evaluated for radiographic bone healing, ulcer healing, recurrence rates, functional outcomes [measured by the Foot and Ankle Disability Index (FADI)], and plantar pressure distribution using pedobarography. Results: We operated on 20 unilateral cases (13 females, 7 males; mean age: 58.6 ± 7.1 years; diabetes duration: 11.3 ± 1.9 years). Radiological union occurred in 34.4 ± 2.1 days, with fibrous union in 15% of cases, though clinical stability and functional improvement were maintained. The average ulcer healing time was 17.05 ± 1.86 days, with complete healing in all patients and no recurrences during follow-up. Functional outcomes improved significantly, with FADI scores increasing from 47.3 ± 7.9 preoperatively to 81.6 ± 4.9 postoperatively (p < 0.001). Pedobarographic analysis revealed a postoperative reduction in plantar pressures under the great toe. Two patients experienced localized infections, which were managed successfully with antibiotics. Conclusion: Minimally invasive proximal phalanx osteotomy is an effective and safe technique for treating recurrent plantar DFUs, significantly improving ulcer healing, functional outcomes, with a low recurrence and complication rate.